Ґенеза тіньових економічних відносин - Хом’як, К. А. (Видавництво Львівської політехніки, 2015)
Здійснено аналітичний огляд літературних даних про виникнення і розвиток тіньової економіки. Визначено підходи щодо трактування поняття “тіньова економіка” з боку вітчизняних та зарубіжних науковців. Обґрунтовано поняття і сформульовано визначення тіньової економіки, розкрито умови кризових явищ під час її функціонування. Підкреслено необхідність проведення заходів детінізації в Україні. Ukraine’s economy is affected by a number of negative factors that threaten the financial, economic and national security of the country in general. One of these factors is shadow economy. At the end of the past century it was a minor secondary phenomenon but having expanded today it transformed into a key urgent problem of economic reality. An important task today is to resist such a negative phenomenon as shadow economy, which is dynamically developing, creating a number of problems for Ukraine. So, to objectively assess this phenomenon and to effectively fight with it, it is necessary to investigate the origins and the evolution of the category of “shadow economy”. Thus, research into the theoretical basis of the phenomenon is of great practical importance for counteracting it. Theoretical and methodological basis of research consists of the works of foreign and domestic scientists who highlighted the wide range of associated problems. In particular, the following are foreign experts who have been studying the phenomenon of shadow economy: K. Hart, D. Blades, P. Gutmann, A. de Soto, E. Feige, F. Schneider, J. Latova and others. Among domestic researchers working in this sphere there are Z. S. Varnaliy, I. I. Mazur, V. O. Turchynov, Ya. A. Zhalila and others. Despite a lot of research done there has not yet been formulated a unified definition of the term “shadow economy”. The purpose of this research is to perform a comprehensive analysis of the concepts of sources and development of shadow economy to get a deeper understanding of this phenomenon, to substantiate causal connections between the events of shadow economy and the official economy. The research is conducted using the historical method and the method of terminological analysis. Chronology, reasons and premises of the formation of shadow economic relations were studied. The interpretation of the definition “shadow economy” was analyzed. It was determined that approaches to studying the shadow economy are different in Ukraine and abroad. To be more detailed, Ukrainian scholars use the theoretical approach according to which the shadow economy is described as an economic category, while foreign scholars apply operational approach that explains shadow economy through its actions and measurements. Due to the absence of a common definition of the shadow economy, we propose a generalized definition, which gives a more comprehensive description of this concept. It is found that shadow economy is a complex, ambiguous and negative phenomenon that requires detailed studying. Perspectives for further research are to examine in detail reasons and factors that stimulate economic entities to resort to shadow economic actions; to develop effective methods of legitimizing the national economy.
Genesis of shadow economic relations
Keywords: тіньова економіка; ґенеза; лихварство; дефініція; детінізація економіки; shadow economy; genesis; usurious; definition; legitimizing of the economy